2005
DOI: 10.1093/ecam/neh123
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Radiation‐Induced Disturbances of Antioxidant Defense Systems by Ginsan

Abstract: There are numerous studies to indicate that irradiation induces reactive oxygen species (ROS), which play an important causative role in radiation damage of the cell. We evaluated the effects of ginsan, a polysaccharide fraction extracted from Panax ginseng, on the γ-radiation induced alterations of some antioxidant systems in the spleen of Balb/c mice. On the 5th day after sublethal whole-body irradiation, homogenized spleen tissues of the irradiated mice expressed only marginally increased mRNA levels of Mn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…In a variety of cells, ionizing radiation has been shown to enhance the production of reactive oxygen species (ROS) that can induce oxidative damage to vital cellular molecules, including DNA, proteins, and lipids (Sun et al 1998;Han et al 2005;Valko et al 2007). The major enzymatic antioxidants that act to limit the activity of ROS are SOD, which degrades superoxide anion radical, catalase and the GSH redox system, which inactivates H 2 O 2 and organic hydroperoxides (Minhas and Thornalley 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a variety of cells, ionizing radiation has been shown to enhance the production of reactive oxygen species (ROS) that can induce oxidative damage to vital cellular molecules, including DNA, proteins, and lipids (Sun et al 1998;Han et al 2005;Valko et al 2007). The major enzymatic antioxidants that act to limit the activity of ROS are SOD, which degrades superoxide anion radical, catalase and the GSH redox system, which inactivates H 2 O 2 and organic hydroperoxides (Minhas and Thornalley 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of MDA in plasma of rats (as a measure of lipid peroxidation) was enhanced after the injection of carrageenan. This rise was more pronounced in irradiated animals, indicating that exposure to ionizing radiation could have resulted in increased lipid peroxidation which was responsible for this increase in plasma level of MDA (El-Ghazaly and Ramadan 1996;Han et al 2005). In the present study, the level of blood GSH was not significantly affected by exposure of rats to 2 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ginseng has been shown to be strongly radioprotective through its ability to stimulate hematopoietic stem cells (colony-forming unit spleen) and produce a battery of cytokines such IL-1, IL-6, IL-12 and TNF-α. Its was also to be proven in study with mice that ginseng exerted its radioprotective effect through activation of antioxidant defense systems [4,25]. However, this was not seen in PBL cells irradiated in vitro with gamma rays as revealed by this study.…”
Section: Resultsmentioning
confidence: 62%
“…Ben-Hur and Fulder [3] demonstrated that in the presence of partially purified P. ginseng saponin mixture, Chinese hamster V79 fibroblasts are significantly more resistant to subsequent -irradiation as determined by the ex vivo colony forming assay. In the studies of cultured spleen lymphocytes from mice, application of P. ginseng water extract 48 h before -ray-irradiation has been shown to reduce the frequency of DNA double strand breaks, and it also has been demonstrated to reduce the degree of radiation-induced apoptosis in both jejunal crypt cells and hair follicles [25]. In addition, Hsu et al [26] found in ICR mice that the intraperitoneal injection of a Chinese herbal medicine that contains 25% of P. ginseng root before whole-body X-ray exposure (0-5 Gy) markedly enhanced the radiotolerance of bone marrow stem cells and peripheral hematocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The regulations of GPx mRNA level and activity by ginseng treatment are responsible for Table 5. Growth and development of rat embryos exposed to ginsenoside Rc on embryonic day 9.5 for 48 h in vitro protecting the animal against ROS-inducing radiation and can be applied to therapeutic remedies for a variety of ROS-associated diseases [36]. In our previous study, cGPx mRNA was shown to be expressed during mouse embryogenesis, distributed in specific cells and organs, and to be abundantly expressed in active differentiation sites [37].…”
Section: Discussionmentioning
confidence: 96%